2015
DOI: 10.1016/j.fertnstert.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of seminal leukocytes on in vitro fertilization and intracytoplasmic sperm injection outcomes

Abstract: Using a flow cytometry method, we demonstrated that leukocytospermia does not significantly influence IVF or ICSI outcomes. The same results were obtained by using lower or higher cut-off values for leukocytospermia (from 0.2 to 2 × 10(6)/mL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 40 publications
1
23
0
1
Order By: Relevance
“…All IVF subjects were treated according to standard clinical and laboratory protocols as previously described . The patients received a long gonadotrophin‐releasing hormone (GnRH) analog protocol or a flexible GnRH antagonist protocol with oral contraceptive pre‐treatment.…”
Section: Methodsmentioning
confidence: 99%
“…All IVF subjects were treated according to standard clinical and laboratory protocols as previously described . The patients received a long gonadotrophin‐releasing hormone (GnRH) analog protocol or a flexible GnRH antagonist protocol with oral contraceptive pre‐treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of different subset of seminal leukocytes was not associated to the rate of conception in vivo (Tomlinson et al, 1993), or to the IVF (Tomlinson et al, 1992a) or ICSI outcome (Ricci et al, 2015). The concentration of leukocytes expressing CD45 was, however, negatively correlated with Figure 3 Flow cytometric assessment of sperm 8-hydroxy-2 0 -deoxyguanosine.…”
Section: (A) (B) (C) (D)mentioning
confidence: 99%
“…In this study, independent variables such as female age, male age and semen parameters based on WHO criteria only showed significant statistical relation between percent agglutination time of semenwith pregnancy.In this research, with increasing leukocytospermic severity, the success rate of IVF was decreased, but the difference was not statistically significant, which is consistent with the results of studies. [45][46][47][48][49][50][51][52] In another study by Hasani et al, the effect of leukocytospermia in infertile men on sperm parameters was investigated. The results showed that the sperm motility in the leukocytospermic group had a significant difference between the non-leukocytospermic group and the healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…37 A number of studies have also shown that leukocytospermia has a negative effect on the efficiency of IVF and ICSI, [38][39][40][41][42][43][44] but some studies have also shown that leukocytospermia has no effect on the incidence of pregnancy and fertility after IVF and ICSI. [45][46][47][48][49][50][51][52] Considering the different results obtained from the studies and in view of the prevalence of infertility and the methods of assisted reproduction available and also the failure to carry out a similar study in this regard, this study was conducted to determine the relationship between semen parameters and success rates IVF.…”
Section: Introductionmentioning
confidence: 99%